Strategi Bakteri Probiotik untuk Menekan Pertumbuhan Bakteri Patogen di dalam Pencernaan Kerapu Chromileptes altivelis dengan Memproduksi Beberapa Bakterial Substansi [ Probiotic Bacteria Strategy For Depressing Patogenic Bacteria Growth In Digestion Of Grouper Fish (Chromileptes altivelis) With Producing Of Substancy Bacterial ] - Agustono Agustono; Hari Suprapto; Muhajir Muhajir (Jurnal Ilmiah Perikanan dan Kelautan, 2012)
Abstract The aim of the research is looking for probiotic bacteria strategy for depresing the growth of patogenic bacteria in digestion of grouper fish. Some of anti bacteria can be produced by bacteria, such as protease, bacteriocia (germicidine, pyrocydia, circulin), amilase lipase, and lyzozym. In this case, Bacillus sp. is chosen because it can produce antibacteria againts Vibrio sp. and probiotic multifactor effect, that is enzyme production and competition of nutrient and space.